Development of broad neutralization activity in simian/human immunodeficiency virus-infected rhesus macaques after long-term infection. (13th March 2018) - Gao, Nan; Wang, Wei; Wang, Chu; Gu, Tiejun; Guo, Rui; Yu, Bin; Kong, Wei; Qin, Chuan; Giorgi, Elena E.; Chen, Zhiwei; Townsley, Samantha; Hu, Shiu-Lok; et al.
Abstract : Objective: Nonhuman primates (NHPs) are the only animal model that can be used to evaluate protection efficacy of HIV-1 envelope vaccines. However, whether broadly neutralizing antibodies (bnAbs) can be elicited in NHPs infected with simian/human immunodeficiency virus (SHIV) has not been fully understood. The objective of this study is to investigate whether broad neutralization activities were developed in SHIV-infected macaques after long-term infection as in humans. Design: Neutralization breadth and specificities in plasmas from SHIV-infected macaques were determined by analyzing a panel of tier 2 viruses and their mutants. Methods: Forty-four Chinese macaques infected with SHIV1157ipd3N4, SHIVSF162P3 or SHIVCHN19P4 were followed for 54–321 weeks. Archived plasmas from 19 macaques were used to determine neutralization breadth and specificities against 17 tier 2 envelope-pseudoviruses. Results: Longitudinal plasma from three SHIVSF162P3 -infected macaques and three SHIV1157ipd3N4 -infected macaques rarely neutralized viruses (<25%) within 1 year of infection. The neutralization breadth in two SHIV1157ipd3N4 -infected macaques significantly increased (≥65%) by year 6. Four of six SHIV1157ipd3N4 -infected macaques could neutralize 50–75% viruses, whereas none of macaques infected with SHIVSF162P3 or SHIVCHN19P4 could neutralize more than 25% of viruses after 6 years of infection ( P  = 0.035). Neutralization specificity analysis showed mutations resistant to bnAbs in V2, V3 or CD4bs regions could abrogate neutralization by year-6 plasma from three SHIV1157ipd3N4 -infected macaques. Conclusion: These results demonstrate that bnAbs targeting common HIV-1 epitopes can be elicited in SHIV1157ipd3N4 -infected macaques as in humans after 4–6 years of infection, and SHIV/NHP can serve as an ideal model to study bnAb maturation. Abstract : Supplemental Digital Content is available in the text